Analysis of Caffeine, Tannin and Total Phenol Content of Tea Leaves from Sirah Kencong Blitar Plantation - Dikatoru, Ravendha; Widayanti, Elok; Ikayanti, Retno (Indonesian Journal of Chemical Research, 2024)
Caffeine, tannins, and total phenol are chemical components of tea leaves that are beneficial for the body. Caffeine is a psychoactive substance, tannin is anti-diarrhea, and phenol compounds are antioxidants that prevent free radicals. The purpose of this research was to analyze the levels of caffeine, tannin, and total phenol of tea leaves at Sirah Kencong Blitar Plantation. Determination of the caffeine level was carried out in tea leaves powder using UV-Vis Spectrophotometry method at 273.5 nm wavelength with caffeine as a standard. The determination of tannin and total phenol levels was carried out using the ethanol extract of tea leaves. Tannin was determined by the Follin Denis method using UV-Vis spectrophotometry at 649.9 nm wavelength with tannic acid as a standard. The total phenol was determined by the Follin Ciocalteu method using UV-Vis spectrophotometry at 794 nm wavelength with gallic acid as a standard. Based on the results of the research in tea leaves from the Sirah Kencong Blitar Plantation, the caffeine content was 1.649%, tannin was 7.095%, and total phenol was 34.142%.